Influence of Eu and Sr co-substitution on multiferroic properties of BiFeO3. Issue 11 (15th August 2016) - Mao, Weiwei; Chen, Wei; Wang, Xingfu; Zhu, Yiyi; Ma, Yuhui; Xue, Hongtao; Chu, Liang; Yang, Jianping; Li, Xing'ao; Huang, Wei
Abstract: Pure BiFeO3 (BFO), and Eu-Sr co-substituted BFO samples were prepared by a sol–gel method. The effects of Eu and Sr codoped on the structural, morphological, magnetic and ferroelectric properties were systematically investigated. The X-ray diffraction and Fourier transform infrared spectroscopy reveal that substitution of Eu and Sr at the Bi site results in structural change and single phase formation. The maximum remnant magnetization of 0.287 emu/g and coercive field of 10.305 kOe are observed in the Bi0.85 Eu0.05 Sr0.10 FeO3 sample. The suppression of spin cycloid caused from the structural distortion can play an important role in the improvement of magnetic properties. The Eu and Sr co-doped samples also exhibit good ferroelectric properties, which may be attributed to suppressing the formation of oxygen vacancies by Eu substitution.